Deoxyribonucleic acid and interspecies relationships of the genus Chlorella (Chlorophyceae) - Huß, Volker; Fischer, Gabriele; Kessler, Erich (Plant Systematics and Evolution, 1989)
Phylogenetic relationships within the genus Chlorella were studied by means of DNA/DNA hybridization under both optimal and relaxed reassociation conditions as well as by determination of the thermal stability of hybrid DNA duplexes. The results indicate a relationship betweenC. fusca var.fusca, C. fusca var.rubescens, C. fusca var.vacuolata, and the genusScenedesmus. In addition, the strains endosymbiotic withParamecium bursaria seem to be related with theC. vulgaris/sorokiniana group. The relations between most other species, however, could not be sufficiently resolved by the above methods. This implies considerable phylogenetic divergency within the genus Chlorell

Molecular cloning and expression of progesterone 5β-reductase (5β-POR) from Isoplexis canariensis. - Herl, Vanessa; Fischer, Gabriele; Bötsch, Ralf; Müller-Uri, Frieder; Kreis, Wolfgang (Planta Medica, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.molecu

Molecular cloning and heterologous expression of progesterone 5β-reductase from Digitalis lanata Ehrh. - Herl, Vanessa; Fischer, Gabriele; Müller-Uri, Frieder; Kreis, Wolfgang (Phytochemistry, 2006)
UnivIS-Import:2015-03-09:Pub.2006.nat.dbio.LPB.molecu_5

Nucleic acid hybridization of group N and group D streptococci - Kilpper-Bälz, Renate; Fischer, Gabriele; Schleifer, Karl-Heinz (Current Microbiology, 1982)
Streptococci of serological groups N and D were found to belong to three different 23S ribosomal RNA (rRNA) homology clusters which are not closely related to each other. One cluster includes the group N streptococci:Streptococcus lactis, S. cremoris, S. diacetylactis, and, in addition, two lactobacilli, Lactobacillus hordniae andL. xylosus. The second one is composed ofStreptococcus faecium, S. durans, andS. faecalis with its subspecies. All are members of serological group D. The third group includes the group D streptococciStreptococcus bovis andS. equinus together withS. thermophilus andS. salivarius. DNA-DNA hybridization studies confirm the close genetic relationship within each of the rRNA homology cluster

Progesterone 5β-reductase genes of the Brassicaceae family as function-associated molecular markers - Munkert, Jennifer; Costa, Catarina; Budeanu, Oleg; Petersen, Jan; Bertolucci, S; Fischer, Gabriele; Müller-Uri, Frieder; Kreis, Wolfgang (Plant Biology, 2015)

Recombinant Δ4,5-steroid 5β-reductases as biocatalysts for the reduction of activated C=C-double bonds in acyclic and monocyclic molecules - Burda, Edyta; Kraußer, Marina; Fischer, Gabriele; Hummel, Werner; Müller-Uri, Frieder; Kreis, Wolfgang; Gröger, Harald (dvanced Synthesis & Catalysis, 2009)
UnivIS-Import:2015-04-14:Pub.2009.nat.dbio.LPB.recomb

The VEP1 gene (At4g24220) encodes a short-chain dehydrogenase/reductase with 3-oxo-Δ4,5-steroid 5β-reductase activity in Arabidopsis thaliana L. - Herl, Vanessa; Fischer, Gabriele; Reva, Veaceslav A.; Stiebritz, Martin; Muller, Yves; Müller-Uri, Frieder; Kreis, Wolfgang (Biochimie, 2009)
UnivIS-Import:2015-03-09:Pub.2009.nat.dbio.LPB.thevep